A comparative study on the machining performance of textured cutting tools with lubrication. (16th July 2009) - Lei, Shuting; Devarajan, Sasikumar; Chang, Zenghu
The performance of textured cutting tools with lubrication in machining mild steel is presented. Microholes and microgrooves are made using femtosecond laser on the rake face of uncoated tungsten carbide inserts. Liquid (oil) and solid (tungsten disulfide) lubricants are applied to the textured cutting tools in an attempt to reduce friction and wear. Friction force and friction coefficient are obtained from three measured cutting force components. Tool wear and chip morphology are examined using optical microscope. It is found that textured cutting tools produce coiled chips and reduce friction force by about 20% and chip-tool contact length by about 17%.